ФУНГИЦИДТІ ҚАСИЕТКЕ ИЕ СHAETOMIUM ТУЫСЫНА ЖАТАТЫН САҢЫРАУҚҰЛАҚ ШТАМДАРЫН АРПАНЫҢ ТАМЫР ШІРІГІ АУРУЫНА ҚАРСЫ ҚОЛДАНУ (Experimental biology, 2017)
In this article exploring in laboratory and field conditions fungicidal quality of cellulosadestruction mushrooms Chaetomium against stimuli rooted decay of barley mushrooms Fusarium and Bipolaris. In result antagonistic qualities of mushrooms Chaetomium investigations obtained datum in laboratory conditions there were confirmated on field experiences
Keywords: Fusarium; Bipolaris